A Comparative Study of Different Properties of Commercial Dental Composite Resins in the Market - Golnaz Tayebi; Sajjad Omidian; Sara Abtahi; Alireza Ranjbar Hassani; Yasaman Sherafatmand (Frontiers in Dentistry)
Objectives: Assessment of mechanical properties of composite resins is important since they can affect the clinical performance and longevity of restorations. This study aimed to assess and compare different properties of dental composite resins available in the market.